Analisis Investasi PLTS 8 kWp On-Grid Pada Bangunan Apartemen Pariwisata di Bali - Murti, Ananda Sri; Kumara, I.N.S.; Ariastina, W.G. (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
The potential for Renewable Energy in Indonesia is very high so that the government is committed to making an energy transition towards clean energy with a target mix of 23% by 2025 as stated in the RUEN. One of the easiest RE to develop and build today is the Solar Power Plant (PV). However, until 2022, the portion of the EBT mix has only reached 12.3% and specifically PLTS with a potential of 200 GW spread throughout Indonesia but its utilization is still less than 300 MW. According to ESDM press release data in 2023, the installed capacity for PLTS in 2022 has only reached 271,6 MWp. This condition is also exacerbated by changes in regulations related to the installation of PV system, especially rooftop PV where several incentive points have been removed so that the investment made becomes less attractive to the public. This research aims to find out which PV regulations can provide a mutually beneficial solutions for both the government and society in terms of increasing the renewable energy mix and the perceived impact of investment. This study uses a case study of an installed 8 kWp on-grid rooftop PV located in Tumbak Bayuh Village, Badung. Furthermore, data collection was carried out to conduct investment feasibility of the construction of the rooftop PV using 3 regulatory scenarios, ESDM Regulation No 48 of 2018, ESDM Regulation No 26 of 2021, and ESDM Regulation No 02 of 2024. The methods used in assessing investment feasibility are Net Present Value, Internal Rate of Return, Benefit Cost Ratio, and Payback Period. The final results show that ESDM Regulation No 26 of 2021 provides the most attractive investment feasibility, with the fastest PP in 5.7 years, IRR 16.18%, NPV Rp. 162,920,001, and BCR value of 1.63. However, as a mutually beneficial solutions, ESDM Regulation No  48 th 2018 is worth considering as it provides similar results for BCR and IRR in ESDM Regulation No 26 of 2021 and also can provide a mutually beneficial solutions for both the government and society.